2016
DOI: 10.1155/2016/7417648
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Stimulated Gene 15 Conjugation Stimulates Hepatitis B Virus Production Independent of Type I Interferon Signaling PathwayIn Vitro

Abstract: Hepatitis B virus (HBV) is an important account of infectious hepatitis and interferon (IFN) remains one of the best treatment options. Activation of type I IFN signaling pathway leads to expressions of IFN-stimulated genes (ISGs) which play important roles in antiviral and immunomodulatory responses to HBV or hepatitis C virus (HCV) infection. Our previous studies indicated that ISG15 and its conjugation (ISGylation) were exploited by HCV to benefit its replication and persistent infection. This study was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…ISG12a can inhibit HCV replication through activation of the JAK/STAT signaling pathway[ 43 ]. A recent study has found that ISG15 conjugation can stimulate Hepatitis B Virus(HBV)production independent of Type I IFN signaling pathway[ 44 ]. All these data point out virus-host interaction is of tremendous importance in the battle against virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…ISG12a can inhibit HCV replication through activation of the JAK/STAT signaling pathway[ 43 ]. A recent study has found that ISG15 conjugation can stimulate Hepatitis B Virus(HBV)production independent of Type I IFN signaling pathway[ 44 ]. All these data point out virus-host interaction is of tremendous importance in the battle against virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Viral release: for specific viruses, ISG15 was found to modulate the amount of released infectious viral particles while intracellular viral replication remains intact. Interestingly , whereas the molecular mechanism is unclear, such effects can be either antiviral (for example, dengue virus 2 (DENV-2)) 156 or proviral (for example, hepatitis B virus (HBV)) 157 depending on the type of virus. Viral latency: ISG15 was also shown to maintain viral latency and prevent reactivation of Kaposi's sarcoma-associated herpesvirus (KSHV) infection via the regulation of specific KSHV microRNAs 74,158 with a cytokine storm, and the survival of Isg15 −/− mice could be prolonged when they were treated with TNFα-blocking antibody before infection 76 .…”
Section: Viral Latencymentioning
confidence: 99%
“…HCV has also been described to use ISGylation to favor its replication and develop persistent infections [ 213 , 214 ]. Recently, ISGylation was also associated with increased replication in HBV infections [ 215 ].…”
Section: Viral Evasion Strategies: Blockade Of Ifn Signalingmentioning
confidence: 99%